Minimum income protection in the austerity tide - Sarah Marchal; Ive Marx; Natascha Van Mechelen (IZA Journal of European Labor Studies, 2016)
Scholarly literature is inconclusive on how economic crises impact on minimum income protection. Earlier studies found small increases in the generosity of safety nets at the onset of the crisis. Yet an increased focus on budget austerity substantially altered the social policy context. This paper assesses how minimum income floors weathered the austerity tide following the crisis using purpose-collected data for 23 EU countries. Generally, social assistance benefit trends did not deviate much from pre-crisis growth levels. Yet retrenchment did occur through more technical measures, the combined impact of which was quite significant in some countries.
Keywords: I38; 330; Minimum income schemes; Crisis measures; Reforms; EU member states; Social floor